Syndrome of Reduced Sensitivity to Thyroid Hormones: Two Case Reports and a Literature Review. (28th September 2016) - Anyfantakis, Anastasios; Anyfantakis, Dimitrios; Vourliotaki, Irene
Abstract : Resistance to thyroid hormone (RTH) is an extremely rare dominantly inherited condition of impaired tissue responsiveness to thyroid hormone (TH). Most patients with RTH have mutations in the gene that encodes the β isoform of the receptor of thyroid hormone ( THR- β gene). Mutant receptors are unable to activate or repress target genes. The majority of them are asymptomatic or rarely have hypo- or hyperthyroidism. RTH is suspected by the finding of persistent elevation of serum levels of free T3 (FT3) and free T4 (FT4) and nonsuppressed TSH. We present two cases of RTH diagnosed after total thyroidectomy. The first patient was initially diagnosed with primary hyperthyroidism due to toxic multinodular goiter. The second patient had undergone thyroidectomy for multinodular goiter 16 years before diagnosis of RTH. After thyroidectomy, although on relatively high doses of levothyroxine, both of them presented with the laboratory findings of RTH. Genetic analysis revealed RTH.